The specialization curse: How economic specialization shapes public goods provision. (September 2019) - Barber, Benjamin; Mazaheri, Nimah
Abstract: This paper examines the relationship between economic specialization and government expenditures. We hypothesize that citizens and firms in economically specialized regions pressure politicians to invest in core economic sectors in lieu of spending on public goods that benefit the broader economy, such as education. We investigate our hypothesis through an examination of the United States and India. We confirm a negative relationship between economically specialized U.S. states and education spending, and a positive relationship between economically specialized U.S. states and firm subsidies. Next, we examine the effects of an immediate shock in a region's level of economic specialization by comparing Indian states created from federal bifurcation. We show how the creation of two highly specialized states (Bihar and Jharkhand) from a diversified state (Undivided Bihar) was associated with a decline in education spending but an increase in subsidies for core sectors.